新編中學生考試焦慮因應量表：以潛在類別分析取向探究學生因應組型及預測因子 Coping Scale With Test Anxiety (COSTA) for Adolescent Students: Exploring Coping Profiles and Predictors Through a Latent Class Analysis Approach - 趙子揚 Tzu-Yang Chao (Journal of Research in Education Sciences)
針對特定情境下之壓力因應策略進行探究，是目前對於壓力研究之共識。本研究主要在重新編製中學生考試焦慮因應量表（Coping Scale with Test Anxiety, COSTA），並檢視目前中學生在考試焦慮因應上的組型。在預試階段，本研究編製110題COSTA量表作為預試題本，並以立意取樣從臺灣蒐集253名中學生資料作為預試階段，經由探索性因素分析及試題分析，最後共得到63題12個向度的正式量表，分別為「尋求進步」、「正向認知」、「放棄準備」、「宣洩情緒」、「放鬆行為」、「轉換心情」、「支持改善」、「接受結果」、「朋友相聚」、「安慰想法」、「自我獎勵」及「書寫宣洩」。在正式分析中，以678名中學生之資料進行驗證性因素分析。測量模式上，調整後的12個向度測量模式得到可接受的適配度，而各向度之組成信度介於.56～.87之間，平均抽取變異介於.18～.54之間。本研究進一步將12個向度之平均數進行潛在剖面分析（Latent Profile Analysis, LPA），發現分為七個類別最為適配。接著，本研究進一步進行三階段取向的潛在類別迴歸（Latent Class Regression, LCR），以學生個人屬性，包含性別、年級、班上排名、家庭子女數、家中排行、藏書量、補習天數、平日假日念書時間、睡眠時間、考試焦慮及不確定性，預測七個潛在類別。結果發現，部分個人屬性的確能夠預測不同的因應組型，例如，較不理想的因應組型包含「低因應組」及「放棄並接受組」，有較大的機率是家中藏書量少、週末念書少、考試焦慮較低、不確定性較高，以及班上排名較低之學生。本研究擴充了先前考試焦慮因應的三因素理論，建立更適切的測量工具，亦從組型的觀點看待學生的因應策略，提供較為細緻之檢視，有助於未來因應策略教導之輔導方案。 Objective In countries with High-Stakes Testing (HST) systems, student test anxiety has become a widespread phenomenon. For example, Chao and Sung (2019) reported that 22% of ninth-grade students in Taiwan experience high levels of test anxiety. Therefore, researching how students cope with test anxiety is crucial. Earlier researchers classified individual coping strategies into three main categories: problem-focused coping, emotion-focused coping, and avoidance coping. Chao et al. (2014) developed the Coping with Examination Stress Scale (CESS), which also reflected the three-dimensional coping classification. Although CESS aimed to address the context-specific nature of coping, recent studies have increasingly moved beyond the three-dimensional framework to identify specific coping methods for specific situations, aligning with the person-environment interaction model. Additionally, recent research on coping strategies has shifted from a variable-centered approach to a person-centered approach, emphasizing the heterogeneity within subgroups of the same population. Therefore, the primary purpose of this study is to re-develop the Coping Scale with Test Anxiety (COSTA) for secondary school students by expanding beyond the three dimensions of CESS to include a wider range of coping strategies. During the pretest analysis phase, we aim to retain as many meaningful coping strategies as possible. Another objective of this study is to use the LPA approach to identify different coping patterns among students. Furthermore, we employ latent class regression (LCR) to predict different coping pattern categories based on students’ individual attributes.